Transforming Renal Diagnosis: Graphene‐Enhanced Lab‐On‐a‐Chip for Multiplexed Kidney Biomarker Detection in Capillary Blood - Diforti, Joaquin Felipe (2024)
Chronic kidney disease (CKD) is a significant global health concern, impacting over 10% of the world population. Despite advances in home-based treatments, CKD diagnosis and monitoring remain centralized in large laboratories. This work reports on the development of a Graphene-based Lab-On-a-Chip (G-LOC) for the self-testing of multiple renal function biomarkers in capillary blood. G-LOC integrates bioelectronic sensors with a 3D-printed microfluidic system that enables the multiplex quantification of urea, potassium, sodium, and chloride, from one drop of blood. The potentials of three graphene sensors modified with ion-selective membranes and enzymes are simultaneously measured. The analytical performance of the test is evaluated in terms of linearity, accuracy, and coefficient of variability (CV). Accuracy values higher than 98.7%, and CV values lower than 10.8% are obtained for all the biomarkers. Correlation and Bland–Altman plots show good correlation (slopes in the range of 0.94–1.15) and high agreement of G-LOC with a reference method. It is also demonstrated that the test can correctly differentiate biomarker levels normally obtained for healthy people, early-stage CKD, and end-stage CKD. Finally, user experience is studied with a group of untrained volunteers who highlight the simple usability of the test and its suitability for at-home diagnostics.